Redukcjonizm naukowy i komputerowy a treść świadomości - Żytkow, Jan (Filozofia Nauki, 1995)
Our consciousness is a challenge both for the scientific and the computer reductionism. In the article I show that in everything which appears in our awareness there is an element which cannot be captured by scientific experience and computer models. Because our minds interact with the material world, only interactionism is compatible with our whole experience. But there is no sense to demand that the mechanism of this interaction should be given, because such mechanism cannot exist. Subsequently I reject evolutionary arguments for materialist monism. At the end of the article I point that interactionism does not exclude the posiibility of progress in modeling scientifically external observational aspects of consciousness.